A divided diocese at the end of the Christian world. The case of the bishopric of Włocławek - Maciejewski, Jacek (En la España Medieval, 2022)
The construction of the gothic cathedral church in Włocławek on the new site by the local bishops, after the former one was burned down by the knights of the Teutonic Order in 1329, coincides with a time of political consolidation of the Kingdom of Poland and a significant reinforcement of the power of Polish kings. For that frontier bishopric, situated in the northern part of the country, it was also a period of stabilization and strengthening of diocesan structures. The earlier history of this diocese, however, was marked by divisions and political rivalry, as well as by an interesting institutional dualism. In my paper, I focus my attention on the period between 1123/1124 – 1330 and on showing how local bishops and chapters built the ecclesiastical structures of this long politically fragmented diocese which initially encompassed some areas that had to be christianised. I also intend to show the ways in which Kuyavian bishops dealt with the problem of loyalty to the rulers, sometimes hostile to each other, while maintaining of interests and well-being of their bishopric.